How the Judgement Effective? The Role of United Nations in Conflict Resolution Between Palestine and Israel (Universitas Negeri Semarang, 2021)
The conflict that still occurred between Palestine and Israel is one of the most complicated conflicts in the world, which even until modern times and human rights are increasingly held in high esteem today, the conflict has not yet come to light and cannot be resolved. If in total, even up to millions of victims died due to the conflict both from the parties involved and even the civilian population ranging from toddlers to the elderly. This has invited the sympathy and attention of various countries in the world. However, due to complexity of the conflict, countries on the world that want to help resolve the conflict have not been able to help and contribute optimally. Even the UN, which is a world peace organization, is not yet able to work optimally. Many people accuse that the main cause is the United States. The United States considered to be the mastermind behind the conflict so that the conflict has not been resolved to date. The United States which is an ally of Israel always makes various efforts that are precisely considered beneficial to Israel. Even though they are criticized by various countries, because of their power it does not make America afraid and even stays strong so that countries that condemn American actions cannot do big things as a form of change in accordance with their wishes.